Sleep and diet quality in adolescents - Pereira, Ana Maria Geraldes Rodrigues (2018)
Background: Inability to sleep increases the vulnerability of overeating in particular high calorie density foods considering the current obesogenic environment. In addition, scientific research has shown that a healthy and balanced diet positively influences sleep quality. Objectives: This study aimed to evaluate the quality of sleep of adolescents in the county of Bragança and its association with diet quality. Methods: It was carry out the study in a population of 345 high school students. The data was collected in May 2017 through a questionnaire that included the Pittsburgh Sleep Quality Index (PSQI), by Ramalho (2008). Results: Throughout the study and following PSQI analysis, it was concluded that 39.71% (n=137) of participants showed poor quality of sleep (PSQI >5 points). The correlation between sleep quality and diet quality was assessed and a statistically significant association was found between the quality of sleep and the intake of snacks (X2=17.144; p≤0.001), sugary products (X2=18.603; p=0.000), fast-food (X2=12.353; p=0.002) and ready meals (X2=14.852; p≤0.001). The risk of suffering from poor sleep quality is higher in young populations who frequently eat snacks ([OR]: 2.811; 99%), sugary products ([OR]: 1.901; 95%), fast-food ([OR]: 4.000; 99%) and ready meals ([OR]: 5.621; 95%) in comparison with young populations who rarely eat this sort of food. The sleep quality is also significantly related to the number of correct eating habits (test t = 4.857, p≤0.001). Adolescents with good sleep quality presented a greater number of correct eating habits (mean: 7.85) compared to students with poor sleep quality (mean: 6.55). Conclusions: Through the analysis of the results, the correlation between sleep quality and dietary quality is evident. The risk of having poor quality of sleep is higher in students who frequently eat a high calorie diet and also in students who have fewer healthy eating habits.